Effects of Increasing Oat Groats on Nursery Pig Performance - J. A. Chance; A. B. Lerner; J. M. DeRouchey; J. C. Woodworth; M. D. Tokach; R. D. Goodband; S. S. Dritz (Kansas Agricultural Experiment Station Research Reports, 2018)
In Exp. 1, a total of 225 pigs (241 × 600, DNA, Columbus, NE; initially 13.9 lb BW) were used in a 28-d study to evaluate the effects of increasing ground oat groats on nursery pig growth performance. Pigs were weaned at 21 d of age and randomly allotted to pens and fed a commercial starter diet for 7 d prior to the start of the experiment. Pens of pigs were assigned to 1 of 5 dietary treatments in a randomized complete block design by body weight (BW) with 4 or 5 pigs per pen and 10 pens per treatment. Dietary treatments consisted of 0, 7.5, 15, 22.5, or 30% oat groats added in replacement for corn in the diet. Treatment diets were fed for 14 d with pig weights and feed disappearance collected weekly to determine average daily gain (ADG), average daily feed intake (ADFI), and feed-to-gain ratio (F/G). A common diet was fed from d 14 to 28. Data were analyzed using PROC GLIMMIX with pen as the experimental unit. For the experimental period (d 0 to 14), increasing oat groats resulted in no evidence for differences (P>0.05) in ADG, ADFI, F/G, or d 14 BW. There was no evidence (P>0.05) for treatment differences during the common phase (d 14 to 28) or the overall period. In Exp. 2, a 7-d preference study was conducted to evaluate the response when pigs were given the choice between the diet with 0% groats compared to either the diet with 7.5 or 30% groats. A total of 48 pigs were used with 4 pigs per pen and 6 replications per comparison. Pigs were weighed on d 0 and 7, and feeders were weighed and rotated position within the pen twice daily to determine ADFI of each diet offered. When given the choice, there was no evidence for difference (P>0.05) in ADFI or percentage of diet consumed between the 0 and 7.5% oat groat diets. When given the choice between the 0 or 30% oat groat diets, pigs had increased (P= 0.001) ADFI (0.11 vs. 0.64 lb) for the 30% oat groat diet compared to the diet without oat groats. In conclusion, increasing oat groats in nursery diets did not improve growth performance; however, when given the choice, pigs preferred the 30% oat groat diet compared to diets without oat groats.
Keywords: corn; nursery pigs; oat groats; oats